PEMBELAJARAN ORANG DEWASA DI KABUPATEN PASAMAN BARAT (KASUS KETERAMPILAN MEMBUAT POLONGAN DI CV TULEH JAYA) - Irda Hayati (Universitas Negeri Padang, 2014)
The background of this research is an entrepreneur's success in learning to make legumes. This study aims to describe the learning resources, describe the method of learning, describe a means of learning, learning material depicting, describing the learning environment, and describes the evaluation of adult learning. This study used a qualitative approach in the form of case studies. Data collection techniques in this study is the snowball sampling technique. The collection of data through observation, interviews, and documentation. Analysis of the data used is the analysis of qualitative data. The process is done with the data reduction, the data display, and conclusion drawing / verification.